Numerical modeling for the steady-state condition of the geothermal system in Way Ratai - Karyanto (Tamkang University Press, 2021)
Steady-state model of geothermal system in Way Ratai for exploration activities was numerically modelled by using the HYDROTHERM INTERACTIVE software based on the Newton-Raphson algorithm. In the present numerical modelling, cross-sectional area was determined by around 18 km in length of northwest-southeast (NW-SE) direction and 5 km in vertical direction from a mean sea level (msl) using grids width of 100 m, 200 m, and 500 m. Numerical simulation was run for 100,000 years using an interval 1000 years along with manifestation data as reference current conditions. Significant results of simulation were obtained at a 25,000 iteration years, identifying as steady-state condition for the Way Ratai geothermal system. The numerical results show that geothermal reservoirs potentially has a length range of approximately 9 km, with a thickness of 0.5-1.5 km with a temperature ranging from 250 - 350◦C. The reservoir’s depth is ranging from 600-1200 m beneath thick caprocks and strengthens previous AMT research results. The distribution of steam trapped in the southeastern part of the Way Ratai peak becomes an important target for exploration drilling. Furthermore, according to large area, thickness, and high reservoir temperature from numerical models, the Way Ratai geothermal system is potential to being explored because the geothermal reservoirs contain a high enthalpy mass of steam.